Green Tax Reform and Employment Double Dividend in European and Non-European Countries: A Meta-Regression Assessment - Maxim, Maruf Rahman; Zander, Kerstin K.; Patuelli, Roberto (International Journal of Energy Economics and Policy, 2019)
In this paper we present a meta-regression analysis of simulation studies concerning green tax reform (GTR). Our study investigates the employment effect of GTR across European and non-European countries. The existing literature postulates that employment double dividend (EDD) is achievable; however, the majority of the studies come from European countries. In this paper, we compared the performance of GTR led EDD in European and non-European contexts to observe whether there is any notable difference across country groups. Our results show that both tax and tax revenue recycle policies play a significant role in determining the employment effect. However, the optimal policy mix is not identical for European and non-European countries. Region specific policy design is required for optimal employment effect. Keywords: Green tax reform, employment, employment double dividend JEL Classifications: H23, H21, E24, Q52 DOI: https://doi.org/10.32479/ijeep.7776